Dual roles of lactate and lactylation modification in the nervous system: neuroprotection and neuroinjury - Ran, TianLu; Shen, YunLong; Peng, DeJian; Tang, Li; Pan, ZiHeng; Zeng, XinYi; Liu, Hui (Frontiers in Aging Neuroscience, 2026)
Lactate is the terminal product of anaerobic oxidation within the glucose metabolism pathway. Traditionally, lactate has been regarded as a metabolically insignificant byproduct derived from incomplete oxidation. However, recent evidence suggests that lactate plays dual roles in the nervous system: neuroprotective and neurotoxicity. The diverse functions of lactate in the nervous system are influenced by its varying concentrations and distinct signal transduction pathways. This review focuses on elucidating the molecular mechanisms underlying lactate’s functions through energy metabolism, neurodegeneration, neural excitation, and neuroinflammation, particularly the signaling pathways involved in neuroprotection and neuroinjury. Furthermore, we highlight several pharmacological agents associated with these processes, aiming to provide novel insights and therapeutic strategies for neuroprotection under specific conditions such as hypoxia, and the management of neurological disorders.